1973
DOI: 10.1177/030006057300100217
|View full text |Cite
|
Sign up to set email alerts
|

Standards of Cleansing and Sterilization of Infant Feeding Utensils in the Home

Abstract: Microbiological standards achieved by mothers when sterilizing babies' feeding utensils in the home were studied in the Slough area in England. Results indicated a marked improvement in this aspect of baby hygiene when compared to results of a similar survey conducted in the town of Reading, England, in 1970. Previously, 78% of bottles and 70% of the teats were recorded as being satisfactorily sterilized. During this study the number of sterile bottles had risen to 98.1%, sterile teats to 90.6%. These improved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…The majority did not carry out sterilisation procedures as recommended, in spite of the fact they had received health education in this field. Clegg et al .’s study in England in 1977 (31) found similar results.…”
Section: Resultsmentioning
confidence: 58%
See 4 more Smart Citations
“…The majority did not carry out sterilisation procedures as recommended, in spite of the fact they had received health education in this field. Clegg et al .’s study in England in 1977 (31) found similar results.…”
Section: Resultsmentioning
confidence: 58%
“…The majority did not carry out sterilisation procedures as recommended, in spite of the fact they had received health education in this field. Clegg et al's study in England in 1977 (31) found similar results. The most recent study (18) examined the effectiveness of commonly used cleaning and disinfecting procedures on the removal of enterotoxigenic Bacillus cereus from feeding bottles.…”
Section: Published Literaturementioning
confidence: 55%
See 3 more Smart Citations